2020
DOI: 10.12965/jer.2040050.025
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity exercise improves cognitive function and hippocampal brain-derived neurotrophic factor expression in obese mice maintained on high-fat diet

Abstract: We wanted to find the intensity of exercise that could increase brainderived neurotrophic factor (BDNF) expression and improve spatial learning and memory without dietary control. C57BL/6 mice were fed a 60% high-fat diet (HFD) for 6 weeks to induce obesity. Obesity-induced mice were exercised on a treadmill for 8 weeks at various exercise intensities: HFD-control (n= 7), HFD-low-intensity exercise (HFD-LIE, n= 7, 12 m/min for 75 min), HFD-middle intensity exercise (HFD-MIE, n= 7, 15 m/min for 60 min) and HFD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…As an intracellular protein, PSD95 plays a vital role in neuronal synaptic plasticity and learning and memory functions [46]. A previous study has also found that exercise can inhibit the reduction of BNDF in the hippocampal tissue of an obesity model [47]. The feeding of high-fat diets for 3-month-old mice can trigger the reduction of the PSD95 level [48], and both aerobic exercise and resistance exercise training can up-regulate hippocampal PSD95 expression [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…As an intracellular protein, PSD95 plays a vital role in neuronal synaptic plasticity and learning and memory functions [46]. A previous study has also found that exercise can inhibit the reduction of BNDF in the hippocampal tissue of an obesity model [47]. The feeding of high-fat diets for 3-month-old mice can trigger the reduction of the PSD95 level [48], and both aerobic exercise and resistance exercise training can up-regulate hippocampal PSD95 expression [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Wheel running is also shown to ameliorate memory deficit and amyloid deposition in HFD-fed AD mouse model [ 293 ]. Notably, physical exercise is not only useful in combating a wide range of neurocognitive and neuropsychiatric symptoms in obese and diabetic rodents, including improving learning and memory deficits [ 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 ], reducing depression-like behaviours [ 90 , 304 ], and improving uncontrolled appetitive behaviours in hyperphagia suppression test [ 305 , 306 , 307 ]. Restored adult neurogenesis, improved synaptic plasticity, and reduced neuroinflammation may altogether contribute to cognitive improvements in obese and diabetic rodents [ 66 , 67 , 295 , 308 , 309 , 310 , 311 , 312 ].…”
Section: Physical Exercise-induced Mediators On Promoting Metabolimentioning
confidence: 99%
“…Voluntary wheel running following brain inflammation inhibited proinflammatory cytokine production and apoptosis, then improved spatial learning memory [13]. Performing treadmill running improved spatial learning memory, short-term memory, and recognition memory [26][27][28]. In the current study, induction of AD was found to worsen the spatial learning memory in the Morris water maze task, whereas treadmill running improved AD-induced spatial learning memory.…”
Section: Discussionmentioning
confidence: 46%